miR-3064-5p and miR-4745-5p affect heparin sensitivity in patients undergoing cardiac surgery by regulating AT-III and factor X mRNA levels - Ma, Hai-Ping; Fu, Min; Masula, Maisitanguli; Xing, Chang-Shuang; Zhou, Qiang; Tan, Jing-Tong; Wang, Jiang (Frontiers in Physiology, 2022)
Subject: Peri-operative regulation of coagulation function through heparin in patients undergoing cardiac surgery with cardiopulmonary bypass (CPB) is an important part of performing cardiac surgery, and postoperative bleeding due to abnormal coagulation function caused by differences in heparin sensitivity in different individuals is an independent risk factor for postoperative complications and death. Method: 10 miRNAs interacting with AT-III and FX genes were predicted using online database. Patients were divided into three groups according to the difference in activated clotting time (ACT) after the first dose of heparin (2.5 mg kg-1) : group A: hyposensitive group (ACT < 480s); group B: sensitive group (480s ≤ ACT ≤ 760s); group C: hypersensitive group (ACT > 760s). Peri-operative and 24 hours post-operative blood loss and other clinical data of patients in the three groups were recorded. Blood samples were collected before surgery, and RT-PCR was used to detect levels of AT-III and FX genes mRNA and the levels of predicted 10 miRNAs, Result: Heparin sensitivity was positively correlated with AT-III mRNA levels and negatively correlated with FX gene mRNA levels in the three groups; the blood loss in group B was significantly lower than that in groups A and C, which was statistically significant (P<0.05). miR3064-5p and miR4745-5p expression levels were significantly different among group A, group B and group C (P<0.05).and were closely correlated with AT-III and FX gene mRNA expression levels, respectively. Conclusion: Differences in heparin sensitivity in patients undergoing cardiac surgery were associated with the mRNA expression of AT-Ⅲ and FX genes, and the expression levels of miR3064-5p and miR4745-5p were found to be closely related to the AT-III and FX gene mRNA respectively, indicating that miR-3064-5p and miR-4745-5p affect the differences in heparin sensitivity among different individuals by regulating the mRNA expression levels of AT-Ⅲ and FX genes. TRIAL REGISTRATION: Registration number: ChiCTR-2100047348. Trial registry: China Clinical Trial Registry